THE INFLUENCE OF BELT DIRECTION ON THE CONNECTION OF PRECAST COLUMN- BEAMS WITH CFRP SHEETS - Rante, Harmonis (Jurnal Ilmu Pendidikan Indonesia, 2023)
The precast beam-column connection method with CFRPs can be developed into an applicable splicing method and environmentally friendly, considering its achievement of 90.6% over monolith joints. The existing weaknesses need to be studied further for the improvement of this connection method. The use of belts with a perpendicular U-shape direction apparently causes the effect of edge stress (scissor force) which actually causes premature failure. This study aims to analyze the influence of belt direction on precast beam-column joints with CFRPs, namely attaching diagonal directional belts to the U-shape. Variations of specimens used are monolith connections (MN) as normal specimens, beltless connections (U1-B0), connections with one belt installed perpendicular to U-shape (U1-B1) and connections with one belt mounted diagonally to the U-shape (U1-DB1). The MN joint achieves a load capacity of 24 kN and deflection of 44.7 mm. U1-B0 reaches 21.75 kN or 90.6% with deflection of 31.36 mm or 70.2% against MN. The U1-B1 reaches 15 kN (62.5%) and deflection is 27.10 mm (60.6%). The U1-DB1 connection reached 26.25 kN (109.4%) with a deflection of 47.16 mm (105.5%) against MN. Changing the direction of the belt to diagonal has improved joint performance, increasing load capacity by 175% and deflection by 174% against U1-B1 and achieving more than monolith joints. With the use of diagonal belts, edge stress still occurs but the process is slower so that the U-shape can last longer. A thicker U-shape is needed to overcome edge stress and this is a part that needs further study.